Evaluating One-to-One Scaffolding and Peer–Scaffolding in Mathematics Learning: Which is Effective? - Imam Kusmaryono; Dyana Wijayanti (STAI Hubbulwathan Duri, 2025)
Effective mathematics learning is shaped by teacher-student interactions and a supportive learning environment. Scaffolding, as a pedagogical strategy, plays a vital role in addressing learning difficulties and enhancing student achievement. This mixed-method study employed a sequential explanatory design, combining quantitative and qualitative approaches. Eighty Grade X students participated as research subjects. Data were collected through mathematics achievement tests, classroom observations, and interviews. Quantitative data assessed the impact of scaffolding on learning outcomes, while qualitative data explored interaction patterns within the scaffolding process. The findings indicate that both one-to-one and peer scaffolding significantly improve students' mathematics achievement. One-to-one scaffolding provides direct teacher guidance but tends to foster student dependency due to its unidirectional nature. In contrast, peer scaffolding promotes mutual interaction, collaboration, and knowledge construction among students, fostering greater engagement and autonomy in learning. While both scaffolding methods are beneficial, peer scaffolding offers a more dynamic and cooperative learning experience. It encourages open communication, peer support, and cognitive development through shared understanding. As a result, peer scaffolding is recommended as a more effective approach for enhancing mathematics learning and fostering a collaborative classroom culture.